Patterns of cognitive dissonance in readers’ engagement with characters (ENTHYMEMA, 2013)
Leon Festinger’s account of cognitive dissonance, published in 1957, has become one of the most successful theories in the history of social psychology. I argue that Festinger’s framework—and the research it generated over the last sixty years—can shed light on key aspects of readers’ engagement with literary characters. Literature can invite the audience to vicariously experience characters’ dissonance through an empathetic mechanism, but it can also induce dissonant states in readers by encouraging them to take on attitudes and beliefs that are significantly different from their own. I suggest that there are two strategies—or patterns of reader-response—through which the audience can cope with the dissonance between their own worldview and the characters’: attitude change and imaginative resistance. In the first, readers adjust their own beliefs and values according to what they have experienced and learned in adopting characters’ perspectives. By contrast, in imaginative resistance readers’ worldview prevents them from establishing an empathetic bond with characters. I integrate these hypotheses into a model that builds on theoretical as well as empirical insights into reader-response.